PENGARUH UKURAN PERUSAHAAN, STRUKTUR ASSET, LIKUIDITAS, PROFITABILITAS DAN PERTUMBUHAN PERUSAHAAN TERHADAP KEBIJAKAN HUTANG - Ahmad Fauzan, 11.42, 02. 0054 (Students Journal of Economic and Management, 2013)
This study examine the impact of firm size, asset structure, liquidity, profitability and firm growth on corporate debt policy.This study focused on the firms basic industries and chemicals that are listed in the Indonesia Stock Exchange in 2006-2011. Sampling technique was conducted by purposive sampling and statistical methods used is multiple linear regression.The results of the study show that firm size, profitability and firm growth is insignificant determinant of the corporate debt policy. The Asset structure has positive and significant impact on debt policy, while liquidity negative and significant impact on debt policy. Keywords: debt policy, firm size, asset structure, liquidity, profitability, firm growth